Systemic solutions for the holistic well-being of cities. Processes, results and reflections - Silvia Barbero; Carolina Giraldo Nohra; Cristian Campagnaro (Agathón)
Today, post-industrial cities can be seen as Living Labs, places to experiment with urban innovation strategies, such as Nature-based Solutions, and to regenerate the natural and man-made ecosystems. These actions require a participatory process that applies co-design tools in the context of a quadruple helix approach, ensuring the Living Lab’s long-term resilience. In this context, this contribution intends to examine the implications of the use of co-design tools, from participatory workshops to SWOT mapping, in the specific context of the case study of Mirafiori Sud, in Turin, within the European project proGIreg (2018-2023), with a focus on the co-design experience of a green wall in a public dormitory of the City of Turin.